SOCIALLY RESPONSIBLE INVESTMENT SEBAGAI MOTIF PENERAPAN SUSTAINABLE CORPORATE SOCIAL RESPONSIBILITY - Vera Intanie Dewi (Bina Ekonomi, 2012)
Socially responsible investment (SRI) usually known as sustainable or ethical or green investment is a new type of investment movement in response to social expectations of investors. Social investors are people who want to improve conditions in society by investing their money in shares or mutual fund from companies that doing their practices in environmental, social and governance issues. Thus, SRI is investing that is mindful of the impact on environmental and society of that investment. It is often described to investors as allowing them "to doll by doing goods”. SRI that integrates environmental, social and governance factors into investment decisions, encourage corporations doing Corporate Social Responsibility (CSR) as a part of their strategic business. CSR is a commonly used term today.CSR is about a sustainable commitment by business to behave ethically and contribute to economic development while improving the quality of life of the community and society and doing environmental preservation. With the globalization of the economy, such issues as environmental degradation and violations of human rights are cause social investors to encourage SRI to grow rapidly. And today’s SRI trends in Global Market reveal how SRI is growing in revenue and making Corporate Social Responsibility happen. Therefore, SRI investors had an important role to encourage corporations to improve their practices environmental, social and governance issues as a continuing CSR.Key words: Socially Responsible Investment